Becoming Housed: Autonomy, Embeddedness, and Ambiguity in Housing First Case Management - Buist, Heather (Université d'Ottawa / University of Ottawa, 2021)
Housing First is a housing model aimed at solving chronic homelessness. It works by offering housing to unhoused people without requiring them to get certain treatments, which reverses previous models. In this ethnographic study, I investigated how this program operates on the ground level, by interviewing and shadowing several case managers who work with clients who experience homelessness, addiction, and mental illnesses. What my research reveals are the tensions that emerge in the process of implementing Housing First programs. I explore how case managers shape the client’s choices and their relationships, to see how some forms of autonomy are valued over others and how clients are made to be individuals in some ways and a part of a community in others. Additionally, I show how case managers navigate ethical practice when the needs of the client conflict with the needs of the organizations for which the case manager works. This intervention is thought to be a solution to a widespread social problem. However, in practice, it is a market-based solution that can only work on an individual level. This results in the reinforcement of liberal understandings of autonomy and responsibility that contributed to the creation of homelessness as a social problem in the first place.
Keywords: anthropology; homelessness; autonomy; housing